Preoperative predictors of endometrial carcinoma in patients undergoing hysterectomy for endometrial intraepithelial neoplasia - Neçirvan Çağdaş Çaltek; Hale Özer Çaltek; Mahmut Yassa; Gazi Güner; İlteriş Yaman; İlkbal Temel Yüksel (BMC Cancer)
Abstract Objective Patients undergoing surgery for endometrial intraepithelial neoplasia (EIN) have a high likelihood of concurrent endometrial cancer (EC). Lymph node dissection (LND) may be required during the operation. Our aim was to predict the presence of cancer and identify which patients might require lymph node dissection preoperatively. Materials and methods This study included 172 patients diagnosed with EIN and operated on by gynecologic oncology surgeons between June 2020 and December 2024. Demographic data, imaging findings, examination notes, surgical details, and pathology results were recorded. Initial associations with progression to EC were analyzed using two-sample t-tests and Mann-Whitney U tests for continuous covariates, and odds ratios (OR) with 95% confidence intervals (CI) for categorical covariates. The relationships between Mayo criteria and either LND or endometrial thickness(ET) were evaluated using Fisher’s exact test. All p-values were two-sided. Results A total of 172 patients were eligible for inclusion. Final pathology revealed EIN in 101 patients (58.7%) and EC in 71 patients (41.3%) after hysterectomy. The likelihood of EC increased with age (< 50 vs. ≥50 years: OR = 3.94, 95% CI: 2.00–7.79, p < 0.001). Diabetes (OR: 2.35, 95% CI: 1.15–4.78, p = 0.019) and hypertension (OR: 2.54, 95% CI: 1.36–4.74, p = 0.004) were more frequently observed in patients with EC compared to those with EIN. Univariate analysis identified age ≥ 50, body mass index (BMI) ≥ 35 kg/m², postmenopausal status, diabetes, hypertension, and ET ≥ 14 mm as variables associated with occult EC. Patients with ET ≥ 14 mm had a fourfold increased likelihood of concurrent EC (aOR: 4.06, 95% CI: 1.89–8.75). Forty-four (62%) patients with endometrial cancer met the Mayo criteria, indicating a need for lymph node dissection. Conclusion Age ≥ 50, postmenopausal status, presence of diabetes and hypertension, BMI ≥ 35 kg/m², and ET ≥ 14 mm are strong predictors of concurrent endometrial cancer. These patients should be referred to gynecologic oncology, as they may require lymph node assessment, including lymphadenectomy or sentinel lymph node biopsy.